School Education of Scheduled Castes Population in India : A Statistical Analysis - Vishald. Pajankar; PRANALI P. (JOURNAL OF INDIAN EDUCATION, 2025)
The greatest challenge faced by India since independence is the mainstreaming of socially excluded group like scheduled caste. The scheduled caste constitutes one of the weakest sections of India’s population, from ecological, economical and educational angles. Some primary and secondary schools have been opened in their areas but the number of school going SC children is very less. Many of them are denied education because either there is no school in their villages or they do not get any facilities to attend them. In order to have a greater coverage on the scheduled castes areas it may be necessary to launch increasingly expanding programmes so that most of the villages should be covered by at least a primary school. This paper is an attempt to study the school education status in the scheduled caste communities in India. The study also focused on some education related parameters and highlights the important issues. The data is analysed statistically on some important indicators and parameters.